2017
DOI: 10.3390/ijerph14060665
|View full text |Cite
|
Sign up to set email alerts
|

Coverage and Influencing Determinants of Influenza Vaccination in Elderly Patients in a Country with a Poor Vaccination Implementation

Abstract: The seasonal influenza vaccination uptake of the elderly in Poland is one of the lowest in Europe. Objective: to assess the vaccination coverage and influencing determinants in patients ≥65 years of age. Methods: A cross-sectional study was conducted (November 2015–April 2016) among consecutive patients admitted to a municipal hospital located in the city of Szczecin, North-west Poland. Patients completed researcher-administered, anonymous questionnaires on socio- demographic data/factors related to the vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 36 publications
8
48
1
Order By: Relevance
“…UMs pointed at di culties in communicating with Polish medical staff about the topic of vaccination. This nding corresponds with our previous research about vaccinations in various Polish population groups [37][38] which found that HCWs are not fully providing information about vaccinations. Therefore, front-line HCWs should increase their role in su cient information delivery to UMs regarding this important topic.…”
Section: Phc Access and Vaccine Deliverysupporting
confidence: 91%
“…UMs pointed at di culties in communicating with Polish medical staff about the topic of vaccination. This nding corresponds with our previous research about vaccinations in various Polish population groups [37][38] which found that HCWs are not fully providing information about vaccinations. Therefore, front-line HCWs should increase their role in su cient information delivery to UMs regarding this important topic.…”
Section: Phc Access and Vaccine Deliverysupporting
confidence: 91%
“…The adjusted influenza VCR was approximately 5.2% among older people during the 2016-17 influenza season in Pudong, Shanghai. This rate was not only markedly lower than the rates reported in European countries, [15][16][17][18] the United States, [19][20] Japan, 21 Jordan, 22 and Korea 23 but also lower than the rate reported in Beijing, 24 which is a similarly sized domestic city with an influenza vaccination subsidy policy for high risk groups (school-aged children and older adults aged 60 years. 5 However, a previous study reported that the mean influenza VCR of urban older people in four selected provinces without a vaccination subsidy policy was 4.1%, 25 which was similar to our finding.…”
Section: Discussionmentioning
confidence: 53%
“…These results are consistent with other studies conducted in other countries. [29][30][31] Moreover, our data showed that influenza vaccination was usually received by the same individuals who were vaccinated in the previous seasons. This is in line with a recent systematic review on factors influencing flu vaccination behavior, which include previous vaccination history as one of the key factors, together with age, poor health status, medical service use, receiving knowledge/information from healthcare professionals.…”
Section: Discussionmentioning
confidence: 65%